The Relationship of Matematical Problem Solving with Numeracy Based on Gender of Geometri and Measurement Materials for Fifth Graders - Hidayah, I Fadhilah Dita Nur; Nuraini, Ni Luh Sakinah; ., Yuniawatika (Proceedings Series of Educational Studies, 2024)
The results of the PISA 2022 survey show that the mathematical skills of students in Indonesia is still at low criteria. The weakness of students' mathematical problem solving skills can be the cause of students' difficulty working on questions tested on the PISA test which are at a high level. This can be caused by students not being used to working on questions at a high level or non-routinely. In learning mathematical problem solving, basic mathematical abilities are needed, namely numeracy skills. Students' lack of numeracy skills can result in a lack of understanding in solving mathematical problems. This research uses a quantitative approach with a correlational type of research. Data collection was carried out using the test method. The sample in this study consisted of 91 students in fifth grades at Gugus 2 Kecamatan Plemahan. The results of this study include differences in mathematical problem solving ability between male and female students, there is no difference in numeracy skills between male and female students, and there is a significant relationship between mathematical problem solving ability and numeracy skills in male and female students with a sig value. 0,000 ≤ 0,05. Keywords: gender; numeracy; mathematical problem solving